Cerebral blood flow responses to dorsal and ventral STN DBS correlate with gait and balance responses in Parkinson's disease - Hill, Kylie; Campbell, M.; McNeely, M.; Karimi, M.; Ushe, M.; Tabbal, S.; Hershey, T.; Flores, H.; Hartlein, J.; Lugar, H.; Revilla, F.; Videen, T.; et al. (2013)
Objectives - The effects of subthalamic nucleus (STN) deep brain stimulation (DBS) on gait and balance vary and the underlying mechanisms remain unclear. DBS location may alter motor benefit due to anatomical heterogeneity in STN. The purposes of this study were to (1) compare the effects of DBS of dorsal (D-STN) versus ventral (V-STN) regions on gait, balance and regional cerebral blood flow (rCBF) and (2) examine the relationships between changes in rCBF and changes in gait and balance induced by D-STN or V-STN DBS. Methods - We used a validated atlas registration to locate and stimulate through electrode contacts in D-STN and V-STN regions of 37 people with Parkinson's disease. In a within-subjects, double-blind and counterbalanced design controlled for DBS settings, we measured PET rCBF responses in a priori regions of interest and quantified gait and balance during DBS Off, unilateral D-STN DBS and unilateral V-STN DBS. Results - DBS of either site increased stride length without producing significant group-level changes in gait velocity, cadence or balance. Both sites increased rCBF in subcortical regions and produced variable changes in cortical and cerebellar regions. DBS-induced changes in gait velocity are related to premotor cortex rCBF changes during V-STN DBS (r = − 0.40, p = 0.03) and to rCBF changes in the cerebellum anterior lobe during D-STN DBS (r = − 0.43, p = 0.02). Conclusions - DBS-induced changes in gait corresponded to rCBF responses in selected cortical and cerebellar regions. These relationships differed during D-STN versus V-STN DBS, suggesting DBS acts through distinct neuronal pathways dependent on DBS location.